Should We Report Incidental Low-Density Liver Lesions with Benign Features? A Retrospective Single-Center Analysis of Trauma CT Scans - Zhang, Bob; Ratnakanthan, Prasanna; Shekarforoush, Maryam; Clements, Warren (Journal of Gastrointestinal and Abdominal Radiology, 2020)
Background Many incidental liver lesions are benign and require no additional workup. Investigation of such lesions can have a negative impact of both the patient and health care system. However, the impact of how radiologists report these incidental lesions is not clear. We aimed to investigate how reporting of incidental liver lesions on trauma computed tomography (CT) scan affects follow-up.Methods This is a retrospective single-center analysis of body CT scans performed following abdominal trauma. Information was collected on the reporting of incidental low-density liver lesions and any additional imaging performed.Results A total of 3,595 trauma body CT scan reports were reviewed. Incidental liver lesions were identified in 527 (15%) patients, with 347 (10%) fulfilling the inclusion criteria. Additional imaging was requested by the referring doctor for 43 out of 285 patients (15%) when lesions were mentioned in the body of the report only, compared with 41 out of 62 patients (66%) when mentioned in the conclusion (odds ratio [OR] = 10.99, p < 0.0001). When additional imaging was recommended in the report, follow-up was arranged for 36 out of 52 patients (69%), compared with 48 out of 285 patients (16%) when it was not suggested (OR = 11.58, p < 0.0001). Additional imaging was requested for 84 of the 347 patients (24%), with 24 of these performed at our institution. All patients followed-up at our institution were diagnosed with a benign lesion.Conclusion Reporting incidental hypodense liver lesions in the conclusion or specifically recommending further additional imaging, both led to significantly increased likelihood of additional imaging being performed. Radiologists who encounter such lesions should consider excluding them from the conclusion if there are no malignant features or patient risk factors.
Keywords: Incidental; liver; benign; cyst; trauma